Linkage analysis of neurofibromatosis. Issue 9 (September 1987) - Kittur, S; Lubs, M L; Bauer, M; Chakravarti, A; Kazazian, H
Abstract : Linkage analysis of neurofibromatosis was performed using genes on chromosomes 1, 8, 11, and 12. No linkage was found between NF and C-myc, AT 3, IGF-1, PTH, and gamma globin genes. Evidence for linkage was found between C-ets 1, on the long arm of chromosome 11 and NF in two families with a lod score of 1.88 at theta = 0. More families are being studied to confirm this linkage.